Learning organization in New Zealand and Malaysian manufacturing companies - Mohd-Zainal, Affandi (Institute of Electrical and Electronics Engineers, 2011)
This paper presents a comparison between learning organization culture in New Zealand and Malaysian manufacturing companies. Learning organization was measured by using Watkins and Marsick ’s Dimension of Learning Organisation Questionnaire (DLOQ) survey questionnaire. The collected data were analysed to assess the reliability and validity of the measurement score of the DLOQ. The data were further analysed so as to determine the differences between New Zealand and Malaysian companies with respect to the presence of a learning organisation-oriented culture. Results of the analysis show that DLOQ are equally reliable and valid in both New Zealand and Malaysian manufacturing context. It was also found that there are significant differences between New Zealand and Malaysia in several dimensions of learning organisation; namely team learning, dialogue inquiry and empowerment. The differences may be attributed to cultural differences between New Zealand and Malaysia.